Analisis Pengaruh Media Sosial terhadap Keberagaman Bahasa: Campur Kode sebagai Tren Komunikasi Anak Muda - Elma Natalia Purba; Diah Pasyha Togatorop; Asima Simbolon; Yuliana Sari (Universitas Palangka Raya, 2024)
The purpose of this study is to evaluate the influence of social media on language diversity, with a special emphasis on the phenomenon of code mixing, which is now a communication trend among Indonesian youth. Young people use code mixing to express their social and cultural identities in an international society. This study aims to understand how social media influences communication patterns and language diversity, and how code mixing impacts the socio-linguistic dynamics of young people. In addition, code mixing, which combines elements of Indonesian and English in conversation, has become part of everyday communication styles, especially on social media such as Instagram, TikTok, and WhatsApp. This study is also important to understand how social media influences communication patterns, language diversity, and the impact of code mixing on the socio-linguistic dynamics of young people. This research uses a qualitative descriptive method to analyze the phenomenon of code mixing in young people's communication on social media. This qualitative approach is considered appropriate because it allows researchers to explore in depth the use of language in a particular social context.The use of code mixing in young people's communication is not just a trend, but reflects changing attitudes towards language. On the one hand, code mixing can be considered a form of linguistic creativity to enrich language diversity, young people use code mixing to express self-identity, openness to foreign cultures, or show affiliation with certain communities.